Efficiency of CROBEX and CROBEX10 stock markets indices - Armin Habibovic; Davor Zoricic; Zrinka Lovretin Golubic (UTMS Journal of Economics, 2017)
The work of Haugen and Baker (1991) and Grinold (1992) has shown that market capitalisation-weighted indices are not mean-variance efficient. Further research by Amenc, Goltz, and Le Sourd (2006) proves that even naïve equal weighting can offer a better risk to return trade-off to investors in the developed markets. Based on earlier research findings of Zoricic, Dolinar, and Kozul (2014) and Dolinar, Zoricic and Kozul (2017) for the Croatian market which demonstrated that outperforming the cap-weighted index in an illiquid and undeveloped market is much more challenging the aim of this paper is to assess the efficiency of both CROBEX and CROBEX10 stock market indices. Efficient frontier was derived based on historical data ('ex post') for 5 revisions for each index. The distance from the efficient frontier was calculated revealing weaker efficiency but also greater diversification opportunities in the case of the broader CROBEX index. However, lower efficiency gains and higher estimation error in emerging market environment reduce significantly the out-of-sample potential for efficient index benchmarks. The analysis conducted in this paper makes it hard to assess if such potential truly exists but provides an insight based on calculation of indifference transaction costs following the work of Amenc et al. (2011).
Keywords: G11; G12; 330; cap-weighted indices; index efficiency